2005
DOI: 10.1111/j.1748-7692.2005.tb01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel Variation in Echolocation Behavior of Wild Harbor Porpoises

Abstract: The echolocation rate and behavior of wild harbor porpoises were studied using a harbor porpoise click detector (POD) deployed close to the bottom at 40 m depth in Scottish waters, UK, April—June 2001. Echolocation variables were compared among four diel phases; morning, day, evening, and night. The echolocation encounter rate, the minimum interclick interval per train, and the proportion of echolocation click trains with a minimum interclick interval below 10 msec were all significantly higher at night than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
134
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(148 citation statements)
references
References 16 publications
13
134
1
Order By: Relevance
“…Click rates were comparable with those reported for Heaviside's dolphins (ICIs of 2 to 113 ms; Morisaka et al, 2011) and harbour porpoises (MICIs up to 120 ms; Carlström, 2005). It is possible that the very few click trains with mean ICI values above 167 ms represent false positive detections.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Click rates were comparable with those reported for Heaviside's dolphins (ICIs of 2 to 113 ms; Morisaka et al, 2011) and harbour porpoises (MICIs up to 120 ms; Carlström, 2005). It is possible that the very few click trains with mean ICI values above 167 ms represent false positive detections.…”
Section: Discussionsupporting
confidence: 65%
“…Click trains from Heaviside's dolphins at Pelican Point displayed higher mean ICIs during the daytime than at night, indicating that clicks were produced at faster rates during the night. Click trains with lower ICI values have been associated with the investigation of objects at close range and feeding (Akamatsu et al, 2005;Carlström, 2005;Verfuβ et al, 2009). In a study of harbour porpoise click behaviour in Scotland, Carlström (2005) reported a peak in mean MICI per train at night and suggested that this slower click rate indicated that porpoises used their echolocation to explore their surroundings at greater distances during the night than in the day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible explanation of the lack of difference in cell density could be that they rely more on vision than first assumed (Teilmann et al, 2007). This is supported by the fact that harbor porpoises have been found to click more during the nighttime (Otani et al, 1998;Carlstrom, 2005).…”
Section: Discussionmentioning
confidence: 85%